Proprotein Convertases - Mbikay, Majambu; Seidah, Nabil G.; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 2011)
Today, activation endoproteolysis of secretory proteins is recognized as a fundamental biological mechanism of spatial and temporal regulation of protein activity as well as of diversification of protein functions.  In Proprotein Convertases, experts in the field examine detailed methods involving proprotein convertases, the enzymes mediating this endoproteolysis, which reside within or cycle between the various compartments of the secretory pathway.  Providing a timely assessment of impact of activation/inactivation endoproteolysis in the secretory pathway, the volume offers a broader perspective on the biochemistry of the PCSKs (proprotein convertases, subtilisin/kexin-type) by exploring structural and functional analogies with bacterial subtilisin and on the enzymology of endoproteolysis itself by describing the involvement in the process of non-PCSK-type such as cathepsin L.  Written in the highly successful Methods in Molecular Biology series format, chapters include introductions to their specific topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and tips on troubleshooting and avoiding known pitfalls.   Meticulous and up-to-date, Proprotein Convertases represents an instructive and useful reference book for all scientists interested in endoproteolytic activation and/or inactivation of secretory proproteins through limited proteolysis, for experts in the field and newcomers to it as well.
On the Discovery of Precursor Processing -- The Prohormone Theory and the Proprotein Convertases: It Is All About Serendipity -- The Proprotein Convertases, 20 Years Later -- Insights from Bacterial Subtilases into the Mechanisms of Intramolecular Chaperone-Mediated Activation of Furin -- The Novel Role of Cathepsin L for Neuropeptide Production Illustrated by Research Strategies in Chemical Biology with Protease Gene Knockout and Expression -- In Vitro Assay for Protease Activity of Proprotein Convertase Subtilisin Kexins (PCSKs): An Overall Review of Existing and New Methodologies -- Inhibitor Screening of Proprotein Convertases Using Positional Scanning Libraries -- Analyses of PCSK9 Post-Translational Modifications Using Time-of-Flight Mass Spectrometry -- The Molecular Biology of Furin-Like Proprotein Convertases in Vascular Remodelling -- Identification of the Myosin Heavy Polypeptide 9 as a Downstream Effector of the Proprotein Convertases in the Human Colon Carcinoma HT-29 Cells -- Regulation of 7B2 mRNA Translation: Dissecting the Role of Its 5’-Untranslated Region -- Analysis of Epigenetic Alterations to Proprotein Convertase Genes in Disease -- Genetic and Functional Characterization of PCSK1 -- Prohormone Processing in Zebrafish -- Use of Zebrafish and Knockdown Technology to Define Proprotein Convertase Activity -- Characterization of Impaired Processing of Neuropeptides in the Brains of Endoproteases Knockout Mice -- Quantitative Peptidomics of Mice Lacking Peptide-Processing Enzymes -- A Proteomic Protocol to Identify Physiological Substrates of Proprotein Convertases -- Neurophenotyping Genetically-Modified Mice for Social Behavior.
Keywords: Biochemistry; Enzymology; Biochemistry, general; Enzymology